Clinical characteristics and visual outcomes of animal-induced ocular injuries: a prospective multicenter study in Iran - Mohammadi, Mohammad; Attar, Alireza; Mahmoudinezhad, Golnoush; Shahesmaeilinejad, Armita; Zhu, Dagny; Fowler, Brian; Farsi, Yeganeh; Shirvani, Mohammad; Gohari, Mohsen (Frontiers in Medicine, 2024)
Background Animal-induced ocular injuries represent an under-documented health problem that may pose significant visual complications. This study aimed to investigate the clinical characteristics and outcomes of ocular injuries caused by animals. Methods This multicenter prospective study enrolled patients with a history of animal-induced ocular injuries presenting to the ophthalmology departments of two tertiary hospitals over a one-year period. All participants underwent comprehensive assessments by ophthalmologists, and the following data were collected: demographic information, animal species involved, injury details, pre- and post-treatment visual data, management strategies, and follow-up outcomes. Results Seventy-two patients (62.5% male) were included in the study. Insects were the most common species, causing 37.5% of ocular injuries. The type of animal involved was significantly associated with injury patterns (p < 0.0001), visual impairments at presentation (p < 0.05), and need for surgery (p < 0.001). Insects predominantly caused periorbital soft tissue injuries; birds primarily affected the anterior segment; dogs and cats mainly led to adnexal injuries; and equines often involved both anterior and posterior segments. Equine-related injuries resulted in the most severe visual impairments, requiring surgical interventions in all cases. At the same time, the majority of cases involved with other animal species experienced no visual impairment. The number of patients without visual impairment increased from 46 cases (63.9%) at the time of presentation to 58 (80.6%) at discharge after treatment. At follow-up, eight patients (11.1%) experienced complications, including traumatic cataract (n = 6, 8.3%), endophthalmitis (n = 3, 4.2%), corneal scarring (n = 1, 1.4%), and retinal detachment (n = 1, 1.4%). Rooster pecking was the leading cause of complications, including endophthalmitis and traumatic cataract. Conclusion This study revealed that depending on the type of animal causing the injury, animal-induced ocular injuries present with diverse characteristics, requiring appropriate treatment approaches and potentially resulting in different outcomes. These findings may promote public awareness and improve preventive strategies and clinical guidelines development.